Assessment of PEFR and FEF25-75 in Female SLE Patients and their Relationship with Duration of the Disease (Bangladesh Journal of Medical Science, 2014)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disorder which affects multiple organs of human including lungs. Objectives: To assess PEFR and FEF25-75 in SLE patients and to correlate them with the duration of the disease.Method: This cross-sectional study was carried out in the Department of Physiology, BSMMU, Dhaka, from January 2010 to December 2010. A total number of 120 female subjects were selected, among which 30 were age and BMI matched apparently healthy subjects for comparison (control) and 90 were patients of SLE (study group). All the patients were matched for age, sex and BMI. Based on the duration of the disease, patients were subdivided into B1 (1-6 months), B2 (2-5 years) and B3 (6-10 years). Controls were selected from the community and the patients from the Out Patient Department (OPD) of SLE clinic, Department of Medicine, BSMMU, Dhaka. (PEFR) and FEF25-75 of all the subjects were measured by a Digital MicroDL spirometer. For statistical analysis Independent Sample t test, One way ANOVA test and Pearsons correlation coefficient test were performed as applicable.Results: The mean percentage of predicted values of lung function parameters in healthy female subjects were within normal ranges. The mean percentage of predicted values of PEFR and FEF25-75 were significantly lower in all study groups when compared to control. Again, the mean percentage of predicted values of PEFR and FEF25-75 were significantly lower in the patients of Group B3 compared to Group B2. Moreover, these comparisons were significantly lower when compared to Group B1. The differences of the mean percentage of predicted value of PEFR, FEF25-75 were non-significantly lower in Group B2 when compare to Group B1. In addition, FEF25-75 were positively correlated with duration of SLE in group B2 but negatively correlated in B3. On the other hand PEFR was negatively correlated with duration of SLE in both B2 and B3. All these values were statistically non-significant. Conclusion: These pulmonary functions decrease in SLE female and the reduction is inconsistently associated with duration of the disease. DOI: http://dx.doi.org/10.3329/bjms.v13i4.20588 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.416-420